Islam Dan Ekonomi Digital Pandangan Historis Kontemporer - Aprilia Kartika; Rania Putri; Ahla Wati; Anisya Anisya; Dwi Noviani (Journal of Innovative and Creativity, 2025)
The relationship between Islam and economics from a historical perspective highlights the values, principles, and evolution of Islamic economic practices from the time of the Prophet Muhammad (peace be upon him) to the modern economic era. The book Islamic Economics (Amar, 2016) serves as the primary reference to explain the conceptual and normative framework of Islamic economics. This study employs a qualitative approach based on historical literature studies and content analysis of classical sources (the Qur'an, Hadith, and books on Islamic jurisprudence) as well as modern academic literature. The results show that Islamic economic principles, such as the prohibition of usury, social justice, and wealth distribution, have become the basis for the formation of an economic system oriented towards social welfare (maslahah). In the modern context, these values are reinterpreted in the form of Islamic financial institutions, Islamic capital markets, and redistribution policies through zakat and waqf. Therefore, a historical understanding is crucial to ensure the relevance and authenticity of the application of Islamic economics in the contemporary era. The development of digital technology has brought about major changes in the global economic system, including in the economic practices of Muslims. This article aims to review the relationship between Islam and the digital economy from historical and contemporary perspectives. Historically, Islamic economic principles are rooted in justice, balance, and the prohibition of riba (usury), gharar (gharar), and maysir (gambling). In the contemporary context, the digital economy offers significant opportunities to improve the welfare of the Muslim community through sharia-compliant e- commerce, halal fintech, and blockchain-based payment systems. However, these developments also pose challenges in maintaining adherence to Islamic values. This study uses a qualitative approach with a literature review method. The results demonstrate that the synergy between sharia principles and digital technology can create an inclusive, transparent, and equitable economic ecosystem.